Assessment of Severity of Cerebellar Mutism in 4th Ventricular Tumors in Pediatric Age Group - Bassim Ali, Khaled; Abou Elnasr, Ashraf Hesham; Reda Rady, Mohamed; Hashad, Amr M.; Hamdy Ashry, Ahmed (Journal of Neonatal Surgery, 2025)
Background: Cerebellar mutism syndrome (CMS) is a neurological condition following surgery that generally manifests 1-2 days after removal of a midline posterior fossa tumor. Aim of work: To evaluate and compare the severity and occurrence of CMS in pediatric patients with 4th-ventricular tumors after surgery by two different appraches (telovelar&transvermian) and two different positions (sitting&prone) and to assess predisposing factors for the severity and occurrence of CMS. Methods: This prospective study has been conducted on forty-four pediatric patients with age range of 1-12 years old. Patients were subdivided into two groups and prepared for surgery, 22 patients on sitting position where half of the patients were operated by transvermian approach, which the other half by telovelar approach. The other 22 patients were operating on prone position and subdivided equally to be operated by the two approaches. Results: Results revealed that 71.4% of patients with CMS were operated on in prone position, while 28.6% of on sitting position had mutism. An insignificant variation has been observed among both groups. Mutism was detected in 57.1% patients with transvermian and telovelar approaches. Out of 25 patients with epidymomas, 20% developed mutism, 20% with medulloblastoma suffered from CMS. The severity of cerebellar mutism was categorized into two major groups: complete profound (neurological and speech abnormalities) and partial (emotional lability). Conclusion: The sitting position offers advantages like clean surgical field, good access to tumors, minimal retraction, and reduced edema in cerebellar tissue. Prone position offers bloody field, reduced retraction, and increased incidence of CMS